Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1099/00207713-49-4-1417
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of partial malolactic enzyme gene sequences for phylogenetic analysis of some lactic acid bacteria species and relationships with the malic enzyme

Abstract: DNA sequences covering 36% of the mle gene that encodes the malolactic enzyme were determined for 13 strains of lactic acid bacteria, representing Pediococcus, Leuconostoc, Lactobacillus and Oenococcus genera. The sequences were aligned with the corresponding region of mleS in Lactococcus lactis. The phylogenetic distance matrix tree of all mle sequences was compared with the 165 rRNA phylogenetic tree. The analysis showed that the mle fragment evolved more rapidly than the 16s gene and differently. Pediococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 66 publications
(39 reference statements)
1
16
1
Order By: Relevance
“…AluI digestion did not permit discrimination among the strains tested, while RsaI and TaqI highlighted three different mle alleles : one characteristic of strains DSMZ 20284 T , DSMZ 20238, ATCC 8042, ATCC 12697 and ATCC 25740, one charcteristic of pediocin-producing strains and of PG and Pdi11 strains, and another typical of all chili bo isolates. The sizes of the restriction fragments obtained were in agreement with the theoretical analysis of the sequence published (Groisillier & Lonvaud-Funel, 1999) only for the mlef fragments amplified from the group of strains obtained from DSMZ and ATCC (Fig. 2c, Table 3).…”
Section: Primary Metabolism Non-housekeeping Genes : Restriction Analsupporting
confidence: 77%
“…AluI digestion did not permit discrimination among the strains tested, while RsaI and TaqI highlighted three different mle alleles : one characteristic of strains DSMZ 20284 T , DSMZ 20238, ATCC 8042, ATCC 12697 and ATCC 25740, one charcteristic of pediocin-producing strains and of PG and Pdi11 strains, and another typical of all chili bo isolates. The sizes of the restriction fragments obtained were in agreement with the theoretical analysis of the sequence published (Groisillier & Lonvaud-Funel, 1999) only for the mlef fragments amplified from the group of strains obtained from DSMZ and ATCC (Fig. 2c, Table 3).…”
Section: Primary Metabolism Non-housekeeping Genes : Restriction Analsupporting
confidence: 77%
“…Several authors have suggested that there is no correlation between 16S rRNA gene and protein-coding genes when the latter is more dependent on selection pressure (17) or had been horizontally transferred across groups at an earlier stage of divergence (7). However, we could not find evidence of the horizontal transfer of this gene based on the branching order of hdc in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…The S. pombe malate transporter is unable to transport fumarate, although fumarate inhibits the uptake of L-malate (Saayman et al, 2000). The cytosolic NAD-dependent malic enzyme (EC 1.1.1.38) has a high substrate affinity (Km = 3.2) (Maconi et al, 1984) and sequence analysis of mae2p revealed a strong phylogenetic link with other malic and malolactic enzymes (Viljoen et al, 1994;Groisillier and Lonvaud-Funel, 1999). …”
Section: S Pombementioning
confidence: 99%